Polychaetes of commercial interest from the Mediterranean East Coast of Algeria - YOUNSI, M.; DAAS, T.; DAAS, O.; SCAPS, P. (Mediterranean Marine Science, 2010)
Three species of polychaetous annelids are commercially collected, as baits, from natural populations along the coast of Algeria. They are collected by semi-professional bait harvesters supplying a variety of local outlets and are used as bait by local fishermen. Bait harvesters commonly use bleaching liquid (10% in sea water) or a KMnO4 (0.5 to 1% in sea water) solution to force Perinereis cultrifera (Nereididae) individuals out of their algal mat. Hediste diversicolor (Nereididae) and Scolelepis squamata(Spionidae) are dug from intertidal mudflats and sandy beaches. Commercial prices and ways of utilization are given for each species. The necessity for the legislative establishment of a regulatory management plan for worm angling is demonstrated.